Efficiency Calculation Analysis of A-Si:H Solar Cells for Determination of Optimum Filament Temperature in Material Deposition - Endhah Purwandari; Toto Winata (Jurnal ILMU DASAR, 2013)
Solar cell efficiency as a function of the energy gap has been simulated by calculating the output current characteristics of the devices based on the distribution of charge carriers, obtained from the solution of the Poisson equation and the Continuity equation. The hydrogenated amorphous silicon (a-Si:H) based solar cell, has simulated in the form of one-dimensional single junction p/i/n. The junction structure of a-SiC:H/a-Si:H/a-Si:H designed have the thickness of 0,015 μm/0,550 μm/0,030 μm, respectively. For simulation, the energy gap has considered constant in the p and n layers, whereas the i layer varies according to the empirical data of energy gap obtained from the deposition parameters of filament temperature. Simulations performed using the finite element method supported by FEMLAB software. Based on simulation results, obtained the highest efficiency of 9.35% corresponds to the lowest energy gap data of 1.706 eV for layer i. This appropriates to the filament temperature of 800oC and subsequently used as the optimum deposition parameters of the material. Keyword: Energy gap, efficiency, FEM, solar cell, hydrogenated amorphous silicon